Carbon Offsetting in Indonesia’s Hospitality and Tourism Sector: Drivers, Barriers, and Strategic Pathways Toward Net Zero Emissions - Ni Made Ria Kurniasih Astuty; Gede Sri Darma; Agus Fredy Maradona (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The tourism industry represents a major contributor to global greenhouse gas emissions, positioning carbon offsetting as a crucial pathway toward sustainable transition. This study aims to map and synthesize the scholarly literature on carbon offsetting in Indonesia’s hospitality and tourism sector, examining the extent and configuration of sectoral participation in carbon offsetting and analyzing the regulatory, economic, operational, and market-related factors that enable or constrain the adoption and scaling of carbon offsetting across the sector aligning with national net-zero emission 2060 goals. Employing a systematic literature review guided by PRISMA 2020 protocols, 30 peer-reviewed articles published between 2020 and 2025 were analyzed to ensure methodological rigor and replicability. The findings reveal that carbon offsetting practices are largely indirect and voluntary, focusing on reforestation, waste management, and energy efficiency rather than participation in verified carbon credit markets. While policy support and environmental awareness serve as key enablers, adoption remains limited by weak verification standards, insufficient technical capacity, high costs, and low consumer trust. The study concludes that a multi-level governance framework integrating transparent MRV systems, institutional strengthening, and stakeholder collaboration is essential to transform tourism’s potential into measurable contributions to Indonesia’s decarbonization agenda.